The print before photography : an introduction to European printmaking, 1550-1820 - Griffiths, Antony; British Museum Publications Ltd. (London : The British Museum Press, 2016)
A landmark publication that catalogues the history and development of the printed image Gutenberg's invention of moveable type made it possible to print letters. But images could only be printed using two other technologies that were developed alongside letterpress. One depended on wooden blocks which were cut and printed in relief, the other on copper plates into which lines were cut by engraving or etching and were printed on a rolling press. Copper-plate printmaking developed into a huge business employing thousands of people, and dominated image production for nearly four centuries across the whole of Europe. Its processes remained very stable, and a man of 1500 could have walked into a printing shop of 1800 and understood what was going on. During the nineteenth century this world was displaced by new technologies, of which photography was by far the most important.
common types of print collecting -- The complexity of print collecting -- The taxonomy of print collections -- The ideal print collection -- The history of print collecting -- 28. The knowledge and literature of prints -- The first publications on prints -- The beginnings of the print catalogue -- The position around 1700 -- The expert and unpublished knowledge -- The rise of the oeuvre catalogue -- The new wave of publications in the later eighteenth century -- The public collection and exhibition -- 29. The understanding and usage of the print in the art world -- The {grave}constprent': the print as art independent work of art -- {grave}Disegni a stampa' and the chiaroscuro woodcut -- The print as product of the artist's studio -- The rise of painting and the professional engraver -- The print as facsimile -- The print as translation -- The status of the engraver vis-a-vis the painter -- Prints as training material -- Prints as a crutch for the poor artist -- Prints and artistic originality -- 30. The hierarchy of the techniques of printmaking -- Burin engraving -- Mixed engraving and etching -- Miniaturist etching -- Etching for the trade -- The painter's etching -- Girard Audran and the etching of history -- The origin of the method of Bartsch -- Mezzotint -- Stipple and aquatint -- Woodcut -- Tail-piece -- Coda -- 31. The print since 1820 -- Steel plates -- Lithography -- Wood-engraving -- Photography -- The position of the hand-made processes -- The changed understanding of the hand-made printing.
Includes bibliographical references (pages 501-545) and indexes.
Keywords: Prints -- Technique -- History; Prints, European -- 16th century; Prints, European -- 17th century; Prints, European -- 18th century; Prints -- Technique; 21.32 history of the graphic arts